Repeated harvest enables efficient production of VSV-GP - Habisch, Rebecca; Neubauer, Peter; Soza-Ried, Jorge; Puschmann, Eva (Frontiers in Bioengineering and Biotechnology, 2024)
Viral products keep gaining importance in multiple therapeutic fields. Considering the scale and production slot limitations, optimizing the outcome of every manufacturing batch is essential to minimize costs and make this therapeutic modality broadly available to patients. Most manufacturing processes for oncolytic viruses currently in clinical studies are based on a batch process. Here, we evaluated the benefits in terms of titer increase of a repeated harvest approach and compared it to the classical batch production process. While no effect on cell density was observed, the cumulated infectious titer following repeated harvest was over 400 times higher than the evaluated batch process yield. This shows that repeated harvests or perfusion have the potential to boost viral yields and should be considered when deciding on a process format for production.